2023
DOI: 10.1186/s12864-023-09262-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomic analysis of germinating rice seedlings to individual and combined anaerobic and cold stress

Abstract: Background Rice is one of the most important cereals consumed worldwide. Two major abiotic factors affecting rice plants in different growth stages are flooding stress and cold stress. These abiotic stresses can take place independently or simultaneously and significantly affect rice plants during germination and seedling growth. Fortunately, a wide array of phenotypic responses conferring flooding stress and chilling stress tolerance exist within the rice germplasm, indicating the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 192 publications
0
8
0
Order By: Relevance
“…Oxidoreductase activity and transcription regulator activity pathway genes were found to be differently expressed in Alfalfa by RNA-seq analysis in response to cold stress [ 29 ]. Another study in rice found that a higher number of genes involved in oxidoreductase activity might contribute to cold tolerance [ 30 ]. Moreover, the identification of DEGs in Pisum sativum using RNA-seq analyses confirmed that oxidoreductase-related genes were enriched after cold treatment [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidoreductase activity and transcription regulator activity pathway genes were found to be differently expressed in Alfalfa by RNA-seq analysis in response to cold stress [ 29 ]. Another study in rice found that a higher number of genes involved in oxidoreductase activity might contribute to cold tolerance [ 30 ]. Moreover, the identification of DEGs in Pisum sativum using RNA-seq analyses confirmed that oxidoreductase-related genes were enriched after cold treatment [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…While aerenchyma is a key trait for waterlogging tolerance (Mustroph, 2018), it can also be formed in response to other abiotic stresses such as drought (Zhu et al, 2010a), mechanical impedance (He et al ., 1996) and nutrient deficiency (Postma & Lynch, 2011). Likewise, a recent study has determined the significant overlap of transcriptomic signatures between anaerobic and cold stresses in rice (Thapa et al, 2023), suggesting that similar regulatory pathway may modulate adaptation to these stresses.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of two differentially expressed genes (DEGs) datasets involved in submergence tolerance during seed germination from independent studies [ 43 , 44 ] was explored to validate candidate genes (CGs) found in core MQTL loci. A Venn diagram was employed to compare the common genes regulating submergence tolerance detected by two DEGs studies, and the genes located in MQTL regions.…”
Section: Methodsmentioning
confidence: 99%